Unexpected histology – ectopic salivary gland in the false vocal cord - Ravisankar, V.; Segar, Rakshita D. V. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
An ectopic salivary gland is an anomaly where salivary gland tissue is located outside its normal anatomical boundaries. We present a case of a 57-year-old man with no known co-morbidities presenting with the sole symptom of persistent throat pain for six months. Clinical examination revealed a cystic lesion in the vallecula and a smooth mass in the anterior third of the right vocal cord. Contrast enhanced computed tomography (CECT) confirmed the findings. Patient underwent microlaryngeal excision and histopathological examination was suggestive of seromucinous salivary gland tissue. We diagnosed the patient as ectopic salivary gland. To date, only nine cases of ectopic salivary glands in the larynx have been identified, with just three occurring in the false cords, making this patient the fourth reported case. This case highlights the need to consider ectopic salivary glands in falsel cords as a differential diagnosis during evaluation of submucosal masses in the larynx.